2020
DOI: 10.1021/acsomega.0c02060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Benzothiadizole–Thiophene- and Benzothiadizole–Furan-Based D–A−π–A Dyes Applied in Dye-Sensitized Solar Cells: Experimental and Theoretical Insights

Abstract: Three novel donor–acceptor−π–acceptor-type compounds (WS5, WS6, and WS7) were synthesized and investigated in dye-sensitized solar cells (DSSCs) exploring the effect of conjugated linkers on device performance. The new dyes showed strong light-harvesting ability in the visible region with relatively high molar absorption coefficients (>21 800 M –1 cm –1 ). This can be attributed to their intrinsic charge transfer (CT) from the arylamine to the acceptor group. Densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…S1 in ESI †) that using a furan spacer, a higher degree of planarity along the molecule is achieved. 34 The dihedral angle of 20 between the benzothiadiazole unit and the phenyl in YKP-88 is reduced to 0 between the benzothiadiazole unit and the furan in DJ-214, leading to a perfect co-planarity and a better conjugation with the anchoring function. The introduction of the furan unit also induces the emergence of an absorption shoulder between 400-450 nm.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…S1 in ESI †) that using a furan spacer, a higher degree of planarity along the molecule is achieved. 34 The dihedral angle of 20 between the benzothiadiazole unit and the phenyl in YKP-88 is reduced to 0 between the benzothiadiazole unit and the furan in DJ-214, leading to a perfect co-planarity and a better conjugation with the anchoring function. The introduction of the furan unit also induces the emergence of an absorption shoulder between 400-450 nm.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…where a large ∆𝐺 𝑑𝑦𝑒 𝑟𝑒𝑔𝑒𝑛 can promote dye regeneration and increase the J SC [22,45]. As O4 displayed the highest ∆𝐺 𝑑𝑦𝑒 𝑟𝑒𝑔𝑒𝑛 , its photoelectrons will be more easily regenerated.…”
Section: Photovoltaic Parametersmentioning
confidence: 99%
“…Zhu et al proposed a new concept, D–A−π–A dye, a highly efficient and stable organic sensitizer . This structure is not only the optimization of the energy-level structure, absorption spectrum, and photovoltaic performance of the DSSCs but also greatly improves the light stability of the dye . The Gratzel’s team designed a new series of co-receptors and demonstrated the important role of some co-receptors.…”
Section: Introductionmentioning
confidence: 99%
“…32 This structure is not only the optimization of the energy-level structure, absorption spectrum, and photovoltaic performance of the DSSCs but also greatly improves the light stability of the dye. 33 The Gratzel's team designed a new series of co-receptors and demonstrated the important role of some co-receptors. Liu et al also found that, in the same case, the D−D−π−A-type dye molecules have better advantages than the D−π−A dye molecules: the absorption spectrum extends to the longwavelength region, the molar absorption coefficient increases, and the thermal stability is better.…”
Section: ■ Introductionmentioning
confidence: 99%